2010
DOI: 10.1111/j.1551-2916.2010.03811.x
|View full text |Cite
|
Sign up to set email alerts
|

Highly Transparent Pure Alumina Fabricated by High‐Pressure Spark Plasma Sintering

Abstract: Highly transparent pure alumina with an average grain size of 200 nm was fabricated by means of high‐pressure spark plasma sintering. The alumina sintered either at 950° or at 1000°C for 10 min under an applied pressure of 500 MPa had an in‐line transmission of about 64% for a wavelength of 645 nm. The application of high pressure allowed to obtain highly transparent full dense alumina at low temperatures with no considerable grain growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 17 publications
1
54
1
Order By: Relevance
“…However, such high-pressure conditions require creep-resistant, tough, and expensive materials such as silicon nitride or tungsten carbide for tooling as well as the reduction of sample cross-section. [41,42] Carbon fiber-reinforced graphite might be a cheaper, easy-to-machine option.…”
Section: Mechanical Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such high-pressure conditions require creep-resistant, tough, and expensive materials such as silicon nitride or tungsten carbide for tooling as well as the reduction of sample cross-section. [41,42] Carbon fiber-reinforced graphite might be a cheaper, easy-to-machine option.…”
Section: Mechanical Effectsmentioning
confidence: 99%
“…Another approach relies on the application of high pressure, as described in Part 2.1. [42,145] Application of high pressure removes heterogeneities in the microstructure while achieving near theoretical density.…”
Section: Transparent Ceramicsmentioning
confidence: 99%
“…Transparent alumina ceramics were also fabricated using SPS, and the transparency has been improved by optimizing the sintering conditions such as heating rate, 1),2) sintering temperature, 3),4) cation doping, 4) 6) powder treatment 7) and pressure. 8) In particular, Grasso et al 8) recently applied high pressure (500 MPa) during SPS of pure alumina and reported an in-line transmission of 64% at a wavelength of 640 nm for 0.8-mm thick sample. This value is the highest transmission among alumina ceramics obtained by SPS, so that the application of high pressure is one of the most effective ways to obtain highly transparent alumina.…”
Section: Introductionmentioning
confidence: 99%
“…Among the latter, the most popular for transparent ceramics is pulsed electric current sintering (PECS), also known as spark plasma sintering (SPS). 7,8,11,12,14,[17][18][19][20][21] In general, powders for these fast sintering techniques have been loose or freeze dried powders 11,14,15,19,20,22 not necessarily well suited to industrial scale production. Whatever the sintering technique used, increasing focus must be put on industrialization aspects, and especially on the green body fabrication method.…”
Section: Introductionmentioning
confidence: 99%
“…3 In recent years, many advances have been made in production of transparent ceramics by various processing and sintering strategies. 1,[6][7][8][9][10][11][12][13][14] Mainstream ceramic processing techniques rely either on dry 11,14,15 or wet powder processing [1,6,9,13,16]-both allowing production of highly dense green bodies (GBs), one key factor for transparent ceramics-as well as on classic sintering followed by hot isostatic pressing (post-HIP) or novel fast sintering techniques. Among the latter, the most popular for transparent ceramics is pulsed electric current sintering (PECS), also known as spark plasma sintering (SPS).…”
Section: Introductionmentioning
confidence: 99%